The Role of Public Engagement in Achieving Sustainable Tourism: A Case Study of Bukik Tabuah Ecotourism - Alfat, Syervina Nur; Sasmita, Siska (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to explore public engagement as a determining factor in the management of sustainable tourism at Bukik Tabuah Ecotourism. The issue raised is how far the public plays an active role in control and development functions, in line with the participatory principles of ecotourism. Using a descriptive qualitative method and in-depth interviews with ecotourism managers, the Wali Nagari, and the local community, this research seeks to identify the concrete forms of such participation. The results show that public engagement at Bukik Tabuah is crucial and operational, manifested through an effective two-way dialogue mechanism. The main focus of public involvement is on socio-cultural control, which has led to firm agreements in the form of rules prohibiting illegal couples and the carrying of prohibited goods, emphasizing the community's role in maintaining local norms. Furthermore, engagement also includes the supervision role of the Nagari in monitoring potential social impacts and providing suggestions for infrastructure improvements (facilities and infrastructure). Although input is accommodated, its realization is gradual due to priority adjustments. Therefore, Bukik Tabuah Ecotourism proves that public engagement is not merely about conveying aspirations, but serves as a key instrument in maintaining cultural harmony, conducting oversight, and promoting sustainable community-based development.